COMPARATIVE ANALYSIS OF POLITICAL REPRESSIONS OF KAZAKHS AND AHISKA TURKS - Кочиев, Э.Р. (Asian Journal "Steppe Panorama", 2025)
The aim of this study is to study the joint history of the Kazakhs and the Ahiska Turks, who were subjected to repression in the republics of Central Asia in the 1920s-1950s. This comparative analysis was made through the prism of interethnic harmony. Firstly, the main goal was to establish a result through in-depth study of the issue in order to prove a hypothesis and answer research questions in this scientific work. Secondly, to create a basis for the development of civil society in Kazakhstan and improve the state policy of Kazakhstan in this regard, using a common history to strengthen interethnic harmony. This study used quantitative and qualitative methods to collect data. Until now, the number and personalities of repressed Kazakhs and Ahiska Turks has not been fully determined. Observation of the repressed people, interviews, archival data are important components of this study. The actuality and importance of this study is to determine that the joint history of Kazakhs and Ahiska Turks is the basis of the state interethnic policy. The process of rehabilitation and development of civil society in the Republic of Kazakhstan has been launched at the state level today.